PENGARUH MODEL CORE BERBANTUAN MEDIA VISUAL TERHADAP HASIL BELAJAR IPA - I Dewa Gede Suta Widura (Universitas Pendidikan Ganesha, 2018)
This study aimed to determine significant difference of science learning results between group of students who had been taught with CORE course assisted with visual media and group of students with conventional course. Fifth grade students of SD Gugus IV in Gianyar regency in academic year 2017/2018 were chosen as the object of this research.This research was quasi-experimental design and used post-test only control group design. Population of this research was 131 fifth grade students of SD Gugus IV in Gianyar regency in academic year 2017/2018. Researcher used random sampling technique in form of lottery to choose research sample. As the result, fifth grade students of SD Negeri 1 Samplangan and SD Negeri 3 Beng were chosen as the research sample. Data of learning science result were gathered using Objective Test and Essay. Gained data were analyzed using descriptive statistic and inferential statistic (t-test). Result shows tarithmetic is bigger than ttable (tarithmetic 5.447 > ttable 2.000). This shows that there is significant difference of science learning result between group of students who had been taught with CORE course assisted with visual media and group of students with conventional course. The result shows CORE course assisted with visual media gives influence towards fifth grade students science learning results of SD Gugus IV in Gianyar regency. Key words: CORE model, visual media, science learning result.